(Re) Examining the Functions of Dùndún Talking Drum in the Inter-Cultural Music Process of Africa and the African Diaspora - Ògúnsànyà Adéolú O. (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
Whenever the hourglass-shaped drum ’Dùndún’ is mentioned, minds of music scholars readily go to the hourglass-talking drum of the Yorùbá-speaking people of West Africa. However, this does not mean that this musical instrument is peculiar to the Yorùbá as its distribution- in its varied forms- across West Africa is general; covering an area stretching roughly from Senegal to the Cameroun Republic1. This talking drum’s compositional and performance techniques have become highly specialized and standardized because of its high usage in both the social and religious celebrations of the Yorùbá. This paper focuses on the use of Dùndún to perform other sonic functions beyond Yorùbá speech melodies and oral poetry. Intercultural music theory, being used in this study has shown that the prospect of Dùndún talking drum usage within the context of diasporic music performances proffers greater potential for the instrument as it has been favourably utilized by internationally renowned musicians in contemporary popular music both within and outside the shores of Africa. Furthermore, that interested musicians in the diaspora will find this instrument useful for their subsequent compositions and performances will help redefine the socio-cultural worldview of the music of Africa.